Theoretical investigation of selective ligand binding mode of galanin receptors. Issue 23 (19th December 2022) - Khan, Salman Ali; Zia, Komal; Ashraf, Sajda; Khan, Alamgir; Ul-Haq, Zaheer
Abstract: The Galaninergic system consist of Galanin and its receptors, involved in neuromodulation and neurotransmission. Galanin regulate its physiologic and pathologic functions by interacting with three G-protein coupled receptors; GalR1, GalR2 and GalR3. The widespread distribution of Galanin and its receptor subtypes in central and peripheral nervous system makes them an attractive drug target for the treatment of neurological diseases. However, subtypes selective ligands paucity and little structural information related to either Galanin receptors and Galanin receptor-ligand complexes hampered the structure-based drug design. Thus computational modeling characterization strategy was utilized for Galanin receptor 3D structure prediction and subtypes ligands binding selectivity. Reported ligands with experimental activity were docked against the homology model of Galanin receptors. Further, the MD simulation and binding free energy calculation were carried out to determine the binding interactions pattern consistency and selectivity towards receptor subtype. Results of binding free energy of per residue indicate key contribution of GalR1 Phe115 and His267 in the selective binding of ligands while Tyr103, Tyr270 and His277 play major role in the selective binding of GalR3 ligands. Our study provide rationale for further in silico virtual screening of small molecules for the development of selective ligands against Galanin receptor subtypes. Communicated by Ramaswamy H. Sarma